Expert Consensus on the Management of Obesity in Older Adults (2026 Edition) - Qi Pan; Lixin Guo (AGING MEDICINE, 2026)
ABSTRACT Obesity in older adults has become a prominent public health issue. Owing to age‐related physiological changes and multimorbidity, obesity in this population is associated with complex clinical manifestations and markedly increased difficulty in management. Based on this, a multidisciplinary panel of obesity experts from Beijing Hospital, National Center for Gerontology, formulated this consensus after rigorous evaluation and iterative revision. The consensus emphasizes that management of obesity in older adults requires comprehensive assessment according to age and overall health status and should adopt a patient‐centered, individualized, and stratified strategy. By adhering to the principles of safety first, functional improvement, and steady progress, the goals are to reduce visceral fat accumulation, maintain or increase muscle mass, protect bone health, and improve physical function and overall health. Special attention should be paid to sarcopenia in older adults. Adequate intake of high‐quality protein, combined with an individualized resistance exercise program, is an effective strategy for maintaining muscle mass. Selection of weight‐loss medication should be guided by evidence supporting its benefit for obesity‐related complications or comorbidities, with close monitoring of adverse reactions.